Point-of-care HIV RNA testing and immediate antiretroviral therapy initiation in young adults seeking out-patient care in Kenya - Sanders, E; Chirro, O; Oduor, C; Mangi, J; Wahome, E; Price, M; Gelderblom, H; Van Der Elst, E; Graham, S (Lippincott, Williams and Wilkins, 2019)
We evaluated outcomes of an HIV-1-testing intervention using rapid HIV tests followed by point-of-care Xpert Qual testing for HIV-1 RNA. Of 706 young urgent-care seeking participants evaluated, 24 (3.4%) had chronic HIV (antibody-positive), 3 (0.4%) acute HIV-1 (Qual-positive, antibody-negative), and 3 (0.4%) early HIV-1 infection (Qual-positive, antibody-discordant). Overall, 21 (70.0%) diagnosed patients started antiretroviral therapy after a median of 4 days (range 0-71). HIV-1 RNA testing led to an increase in confirmed diagnoses by 25%.